Bar Model: A Beneficial Tool in Learning Percentage - Herani Tri Lestiana; Cici Tri Wanita (EduMa: Mathematics education learning and teaching, 2019)
Percentage is found to be a familiar and challenging topic at the same time. Percentage has many application in daily life, yet many students still find it difficult. It might because many schools teach merely a formal procedure and pay less attention to the understanding of the reasoning behinds percentage ideas. This small study employed a design research and aimed at supporting students in understanding percentage by using bar model. Eleven 6th and 7th grade students of American International School of Rotterdam were participated in this study. A sequence of learning activities was designed to help students construct their understanding of percentage. The activities consisted of some rich contextual problems that lead to the emergence of bar model. The result revealed that the model can help students construct students’ knowledge of the relation among numbers in percentage, and also help them solve percentage problems systematically through some intermediate steps which include benchmarks.